New Mycomya species from South-East Asia (Diptera, Mycetophilidae) - Väisänen, Rauno (Zootaxa, 2014)
Mycomya Rondani specimens from the islands of South-East Asia, i.e. Malaysia, Indonesia and the Philippines, are revised. The paper includes a key to the Mycomya species of the South-East Asian islands. The following six new species are described: M. shimai sp. n. from Java, Indonesia, M. pongo sp. n. from Sabah, Malaysia, and M. apoensis sp. n., M. nakanishii sp. n., M. paraklossi sp. n. and M. yatai sp. n. from Mindanao, the Philippines. The holotypes of M. klossi Edwards from Borneo, Malaysia, and M. minutata Edwards from Sumatra, Indonesia, were examined and their genitalia are described. M. occultans (Winnertz) is recorded from Java, Indonesia.